Making the case for institutional support on designing agroforestry technology models for rehabilitating critical lands - Nuddin, Andi; Arsyad, Muhammad; Putera, Muhammad Ikbal; Nuringsih, Nuringsih; Teshome, Temesgen Tilahun (Forestry Faculty, Universitas Hasanuddin, 2019)
Land and forest management practices in developing countries have resulted in millions of hectares of degraded lands. This is caused by policy implementation unable to synergize between conservation-ecological goals, and the economic needs of farmer households. This study aims to showcase a model for bringing together economic and ecological interests more closely in line with one another. Furthermore, the study also presents an institutional structure of a program that could help to establish agroforestry-based land rehabilitation policies. The research employed includes a combination of Farming Income Analysis and Interpretative Structural Modeling Analysis. The results show that farming income, when employing agroforestry technology is higher than non-agroforestry approaches. Furthermore, agroforestry technology supports critical land rehabilitation and provides conditions for longer term sustainability. Therefore, a programmatic institutional approach is needed to support these dual goals. We identify that a programmatic approach would include: (1) applying conditions of an agroforestry system as a holistic structured unit, (2) improvement of farmer knowledge and skills, (3) increasing the role and capacity of relevant institutions, (4) improving coordination between sectors, (5) developing conservation agriculture systems, (6) improving bureaucratic support systems, and (7) strengthening control and supervision functions. These elements imply that implementation of agroforestry technology requires institutional support in designing policy for critical land rehabilitation, of which would have significant economic and ecological outcomes on critical lands.